(untitled) (Jurnal Ilmu Gizi dan Dietetik, 2023)
Root and tuber are a potential food source that can be used as an alternative for food diversification. The consumption of root and tuber as a staple food can support the fulfillment of nutritional needs based on the concept of balanced nutrition by consuming various kind of food . Meanwhile, food consumption is inseparable from social and economic factors that will affect people’s access towards food. This study aims to analyze the effect of regional social and economic factors towards the situation of root and tuber consumption in Indonesia. The design of this research is cross sectional study using secondary data published by BKP and BPS which includes the consumption of root and tuber, total population, average years of schooling, human development index (HDI), real per capita income, unemployment rate, poverty rate, and GDP per capita. The result showed that the variables studied simultaneously had a significant effect on the consumption of tubers, both in quantity (g/capita/day) and quality (kcal/capita/day) at significant levels of p=0.010 and p=0.008.